Formation of Teamwork Among Future Specialists in the Socio-Economic Field Using Project Technology - Olga Soroka; Svitlana Kalaur; Halyna Leshchuk (Pedagogical Discourse, 2025)
The article aims to reveal the peculiarities of team interaction among future specialists in the socio-economic field using project technology. Scientific and theoretical sources characterizing team interaction are analyzed. The essence of the concepts of «team» and «team interaction» is clarified, and the characteristic features of a team are presented: the presence of agreed goals and values; cohesion and adaptability of the behavior of each team member; developed communication; a flexible role structure; a high level of self-control and distribution of responsibility; the presence of general team and managerial competencies in addition to basic and special ones; recognition of a person as an individual. It has been established that «team interaction» consists of three components: «common goal», «interaction in activity», and «common result». The principles of team interaction are substantiated: collective responsibility; voluntary entry into the team; subjective activity; subject-subject dialogical interaction; increased executive discipline; reflexivity; feedback. It has been proven that project technology is effective in the process of forming team interaction among future specialists in socio-economic professions (social workers, managers, psychologists). Project technology is characterized as an educational technology that represents a complex of interrelated forms, methods, techniques, and means of teaching based on interaction, cooperation, and co-creation of all participants in the educational process, determined by the need to achieve the goals and objectives set during the implementation of the project. The functions of project technology are defined as educational, upbringing, and developmental. The step-by-step structure for implementing project technology by higher education students in the socio-economic field is specified («introduction,» «working stage,» «project presentation and defense,» «final stage»). Recommendations have been developed for organizing project activities for future specialists in the socio-economic field.